Santri, Kopi dan Aktivitas Moderasi di Media Sosial - Dini Safitri (Al-Balagh : Jurnal Komunikasi Islam, 2023)
Santri, coffee and moderation are words that can synergize. The habit of drinking coffee has become a mandatory tradition for students in Islamic boarding schools. This habit then gave rise to the phrase, "Santri if they are not reading the Koran, it means they are drinking coffee". Even if there are students who are unproductive and lazy, they are lacking coffee. Moderation in Arabic is defined as wasathiyyah which refers to a complete paradigm of thinking related to religious attitudes in Islam. However, the word moderation has changed its meaning for Islamic radical groups who are active on social media. Instead of spreading Islamic values kaffah, these radical groups tend to divide Islam in the archipelago. To stem this phenomenon, many santri movements are trying to fight back by making coffee activities that aim to do moderation to restore Islam that is rahmatan lil alamin. The purpose of this study is to provide an overview of the role of students in carrying out religious moderation with interesting activities, with coffee as a loyal friend who accompanies students in activities. The method used is literature study. The results of the study show that students, coffee, and moderation can synergize not only in maintaining the social order of Indonesia as a multicultural country but can also penetrate the empowerment of the economy for the welfare of students.